Apathy - where do we find it and how to treat - R. Gomes; C. Santos; N. Descalço; F. Moutinho (European Psychiatry, 2022)
Introduction Although defined heterogeneously within the literature apathy is classified as a multidimensional deficit with emotional, behavioral, and cognitive domains in which there is a decrease in self-motivated/goal-directed activity. Recently conceptualized as a syndrome but lacking a universal screening tool.